Experimental Study on Pullout Behavior of Coir Geotextiles Based on Transparent Soil - Liangyong Li; Houyang Li; Weiqiang Cao (Applied Sciences)
As green and low-carbon materials, coir geotextiles have a broad application prospect in soil strengthening. In order to clarify the interface characteristics of coir geotextiles, the pullout test is performed on coir geotextiles by using transparent soil technology. The transparent soil is prepared by using fused quartz as the skeleton particle and the mixture of No. 15 industrial white oil and No. 3 industrial white oil as the pore fluid. The results show that the mechanical response of different pullout tests is basically similar, that is, with the increase in pullout displacement, the pullout force first increases rapidly, then slowly increases to the peak value, and then gradually decreases with the fluctuation. The adhesion of coir-geotextile–soil interface is 5.68 kPa and the internal friction angle is 3.43°. The interfacial friction coefficient of the coir geotextiles is unstable, ranging from 0.2 to 0.6. With the increase in normal stress, anchorage length, and pullout rate, the peak pullout force and the thickness of the shear band increase gradually.